Predicting denture satisfaction and quality of life in completely edentulous: A mixed-mode study - Varsha Murthy; K R Sethuraman; Shakila Rajaram; Sunayana Choudhury (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of the study was to evaluate the effect of dentist's communication skills and patient's psychological factors in predicting denture satisfaction and quality of life. Settings and Design: Cohort study. Materials and Methods: Patient-related variables were obtained using questionnaires in both pre- and post-intervention phases. In addition to this, in preintervention phase, lacunae in doctor-patient communication were obtained. Based on this, the postgraduates were trained in relevant communication skills required during complete denture treatment. In postintervention phase, the postgraduates were again followed up for continuation or decay of skills. Statistical Analysis: Mixed-mode approach - quantitative and qualitative analysis. Results: Both groups were similar in psychological parameters, personality domains, denture quality and quality of life at baseline. However, there was significant difference in denture satisfaction (P < 0.001) in both the groups. In the experimental group, denture satisfaction was more (80.4%) and quality of life had improved from baseline to 3 months (P = 0.000). Denture satisfaction was associated with self-efficacy (P = 0.002) and the communication skills of the dentist (P = 0.000). Quality of life was associated with the conscientiousness domain of personality (P = 0.049) and the communication skills of the dentist (P < 0.05). Conclusion: Satisfaction and quality of life with dentures were associated with self-efficacy, conscientiousness domain and the communication skills of the dentist. Denture satisfaction can be predicted by dentist communication skills. Therefore, training in communication skills for complete denture patient management and assessment of the psychological profile of the patient could contribute to the effective patient-centered practice to avoid patient dissatisfaction.